Can motor coordination level predict performance on volleyball skills in youth? (¿Puede el nivel de coordinación motora predecir el rendimiento en habilidades específicas de volea en los jóvenes?) - Blena Marinho; Daniel das Virgens Chagas (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Motor coordination is an underlying capacity to successful performs sport-specific skills. However, it is unknown whether motor coordination level can predict performance on volleyball skills. The main aim of this study was to verify whether motor coordination level, assessed using a generic test, can predict performance on volleyball skill sin youth. Material and methods: A total of 34 adolescent students (mean 14.4± 0.3 years) were recruited. The KörperkoordinationtestFür Kinder (KTK), a generic, non-sport specific test, composed by four tasks (i.e. dynamic balance, hopping, agility and moving sideways skills) was used to assess motor coordination level. Motor performance on volleyball skills was assessed on the basis of two product-oriented tasks: underhand volleyball serve and volleyball serve receiving. A single measure representing the volleyball skills of the participants was adopted. Linear regression models were executed. Results: Regression analysis revealed that dynamic balance, hopping and agility skills accounted for 8.5%, 17.0%and 30.5%, respectively, of the variance in the performance on volleyball skills. In addition, the multiple linear regression model significantly predicted 29.3% of the variance in the performance on volleyball skills. However, only agility skill was a significant predictor of the dependent variable in this multiple model. Discussion: Motor coordination level, assessed using a generic test, can predict performance on volleyball skills in youth. Our findings add to the assumption that KTK test can be a useful motor coordination assessment for supporting making-decisions in different settings, such as school physical education and talent identification programs.